α-Glucosidase Inhibitor Activity of some Indonesian Syzygium Extracts - Emma J. Pongoh; Rymond J Rumampuk; Astin Lukum; Ardi Kapahang (Jambura Journal of Chemistry, 2021)
The leaves and fruits of Indonesian Syzygium spp such as white pakoba, red pakoba and bombongan have been extracted by ethanol. The ethanolic extract was partitioned with polar solvent gradient using n-hexane, ethyl acetate and n-butanol repeatedly. Each fraction was tested for antidiabetic activity and exhibited varying degrees of antidiabetic activity when tested with α-glucosidase method. Antidiabetic test indicated that the ethyl acetate and butanol fractions of the leaves of pakoba white, red pakoba and bombongan has potential as a source of active compounds.